Lag phases in the adsorption of lysozyme to Si(Ti)O2 surfaces in the presence of sodium thiocyanate. Part I. Phenomenology. - Ball, Vincent; Lustig, Ariel; Ramsden, Jeremy J. (Royal Society of Chemistry, 1999)
The adsorption kinetics of hen egg white lysozyme (HEWL) in the presence of NaSCN at pH 7.4 onto Si0.8Ti0.2O2 surfaces were measured by means of time-resolved optical waveguide lightmode spectroscopy (OWLS). The adsorption kinetics were characterized by the presence of a lag phase whose duration decreased with increasing lysozyme bulk concentration. This lag phase was followed by rapid growth of the interfacial protein film which ceased at a surface coverage close to that predicted for a monolayer. At bulk concentrations lower than about 50 µg cm-3, the maximum rate of adsorption was equal to the rate predicted for a transport-controlled process from the solution to the surface and at higher bulk concentrations such lag phases were no longer observed. Storage of lysozyme solution prior to adsorption reduced the duration of the lag phase, but analytical ultracentrifugation measurements showed the absence of significant aggregation even at bulk concentrations of 103 µg cm-3. These features are consistent with an adsorption process requiring the adsorption of a small critical nucleus preformed in solution followed by the completion of the adlayer by a mechanism akin to crystal growth. The size of this critical nucleus was estimated to be of the order of only a few lysozyme molecules.